Labrador Inuit on the Hunt: Seasonal Patterns, Techniques, and Animals as They Appear in the Early Moravian Diaries - Olsthoorn, Thea (Études/Inuit/Studies, 2017)
In 1769 an Order in Council from the British government enabled the Moravians to settle in Labrador. The missionaries laid the boundary stones for their land (ca. 405 km2) in the next year, and established their first mission station (Nain) on the Labrador coast in 1771. The brethren’s accounts of their experiences with the Inuit in the Nain diaries include, besides religious issues, weather and travel reports and descriptions of Inuit hunting grounds and hunting techniques for the fauna of the region. This article focuses on their diary depictions of the two main prey species: the seal and the caribou. Consideration is also given to seasonal variation and availability of these animals during the early years of the mission; data were collected for the years 1771 through 1778. Several clues in the Moravian diaries, which went unrecognized by the missionaries, point to interactions and transformations between human and nonhuman beings (animals, spirits). These indications corroborate the spiritual transgression of category boundaries as an essential feature of traditional hunting methods. En 1769, un décret du gouvernement britannique permit aux frères Moraves de s’installer au Labrador. Les missionnaires posèrent des bornes de pierre autour de leur terre l’année suivante (environ 405 km2), et établirent leur première station missionnaire (Nain) sur la côte du Labrador, en 1771. Les récits de ces frères concernant leurs expériences avec les Inuit dans les carnets de Nain incluent, outre les questions religieuses, les bulletins météorologiques et de voyage, ainsi que les descriptions des terrains de chasse des Inuit et des techniques de chasse de la faune régionale. Cet article porte sur les descriptions que l’on retrouve dans leurs carnets, des deux principales espèces de proies : le phoque et le caribou. Il rend compte également des variations saisonnières et de la disponibilité de ces animaux au cours des premières années de la mission les données ont été recueillies pour les années 1771 à 1778. Plusieurs ...